Evaluation of potential and rate of the germination of wheat seeds (Triticum aestivum L) treated with bifunctional growth regulators under water stress - Oshchepkov, Maxim S.; Kalistratova, Antonida V.; Kovalenko, Leonid V.; Ivanova, Мaria S.; Tsvetikova, Marina A.; Bystrova, Nataliya A.; Kochetkov , Konstantin A. (Emirates Journal of Food and Agriculture, 2023)
The synthetic cytokinins belonging to the class of bifunctional carbamates and oxamates were tested for a biological activity in a wide concentration range of 10-2 M − 10-6 M along with chlorocholine chloride taken as reference. The compounds have a pronounced growth-regulatory activity for wheat seeds (Triticum aestivum L) at the optimal concentration of 10-5 M, at which the germination potential Gp and the germination rate Gr of seeds, as well as resistance to water stress, determined by RWC values reach their maximum values. It was found that the technique of spraying wheat seeds with solutions of the compounds used is more preferable than soaking. Key words: wheat, plant growth regulators, carbamates, oxamates, water stress